The Specifics of J. Locke’s and G. Berkeley’s Philosophical Concepts Interpretation in Modern British Critical Literature - Zagorodniuk, Vyatcheslav (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
The article is devoted to the specifics of understandings of J. Locke’s and G. Berkeley’s philosophical conceptions in modern English-speaking critical sources. Actual approaches to the analysis of the philosophy of New Age in general and British empiricism in particular are shown by the examples from such authors as J. Bennet and M. Ayers. The main difference between British and native researches, is that the first ones use problematic approach. This allows the authors to research contradictory moments in J. Lockes and G. Berkeleys conceptions and to find possible solutions for those contradictions. The analysis of “idea” concept in J. Lockes philosophy, the parsing of the material substance problem and few others are among the main themes of this article